Support-seeking and rehoming pathways differ by surrender circumstances among pet owners - Lexis H. Ly; Shelby E. McDonald; Isain Zapata; Alexandra Protopopova (PLoS ONE, 2026)
Animal shelters aim to divert intake by encouraging pet retention in homes (e.g., support services) or through alternative methods of surrender (e.g., self-rehoming); however, it remains unclear what factors contribute to an owner’s decision to seek pet support services, as well as to select different methods to surrender a pet. Using a sample of U.S. and Canadian public members who rehomed a pet within the past five years (n = 452), the present study identified groups of pet owners who share similar patterns of responses to surrender circumstances using latent class analysis (LCA). LCA revealed three heterogeneous classes of owners distinguished largely by the reason for surrender and the length of ownership (Owner Hardships n = 215, New Acquisitions n = 194, Behavioural Incompatibility n = 43). Comparisons revealed differences across classes regarding the proportion of respondents that sought assistance and the type of assistance sought, the pathways used to surrender, and the concerns reported by respondents during surrender. For example, the New Acquisitions class was more likely to relinquish to a shelter, either as the only method or after attempting to self-rehome their animal. The Behavioural Incompatibility class had the highest proportion of participants who attempted to relinquish to a shelter but ended up self-rehoming, and the Owner Hardships class had the highest proportion of participants who self-rehomed as their only method. In addition, the classes varied in the proportion of respondents who reportedly sought assistance to help keep their pet. Qualitative analysis revealed that respondents wanted or sought a variety of different support services, including behavioural support, part-time care, and veterinary care. Future research should consider the heterogeneity in surrender decision-making when addressing issues of intake diversion from animal shelters.